General contracting service expenses (rev 02) of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding general contracting service expenses (rev 02) of BRAC University new campus project.